2013
DOI: 10.1111/gcbb.12061
|View full text |Cite
|
Sign up to set email alerts
|

Biomass production assessment from Populus spp. short‐rotation irrigated crops in Spain

Abstract: The aim of this study was to evaluate the biomass production potential for the Spanish Iberian Peninsula using the Populus spp. 'I-214' clone under several management regimes and land availability scenarios, and to determine its future contribution to Spanish energy demands.Empirical models were fitted to the data from a network of 144 plots located at 12 sites in the continental Mediterranean climatic regions of the Iberian Peninsula, in which yield was related to climate and soil, as well as to plantation ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 50 publications
2
20
1
2
Order By: Relevance
“…Other results for E. nitens short rotation crops in New Zealand (Sims et al 2001) showed yield range to be from 3 to 7 Mg ha -1 year -1 , in line with the worst site qualities in the present work. Furthermore, the results obtained in this study are very similar to those found in a study using the dominant height GADA model developed by Pérez-Cruzado et al (2013) from stem analysis of the same species. While their model, which was fitted for a stand density of between 1,100 and 1,600 trees ha -1 , presents site index curves of 8, 12, 16 and 20 m at a base age of 6 years, if the results are interpolated to the reference age of 4 years used in the present study the results for the two studies in relation to the dominant height model would be practically identical.…”
Section: Growth and Yieldsupporting
confidence: 87%
See 1 more Smart Citation
“…Other results for E. nitens short rotation crops in New Zealand (Sims et al 2001) showed yield range to be from 3 to 7 Mg ha -1 year -1 , in line with the worst site qualities in the present work. Furthermore, the results obtained in this study are very similar to those found in a study using the dominant height GADA model developed by Pérez-Cruzado et al (2013) from stem analysis of the same species. While their model, which was fitted for a stand density of between 1,100 and 1,600 trees ha -1 , presents site index curves of 8, 12, 16 and 20 m at a base age of 6 years, if the results are interpolated to the reference age of 4 years used in the present study the results for the two studies in relation to the dominant height model would be practically identical.…”
Section: Growth and Yieldsupporting
confidence: 87%
“…In this study, the relationship between the basal area and dominant height projection functions and the site variables described in Table 1 were evaluated. For this purpose, linear, allometric and logarithmic structures (1-3) were tested, incorporating a single environmental variable in each parameter in order to reduce multicollinearity (Pérez-Cruzado et al 2014):…”
Section: Development Of Growth Models Including Environmental Datamentioning
confidence: 99%
“…are well adapted to a wide range of environmental conditions; they grow rapidly at high densities and are suitable for coppice cultivation (Tullus et al, 2009) conditions, yields have reached values between 20 and 25 Mg dry matter (DM) ha À1 year À1 in the Mediterranean (Italy) (Mareschi et al, 2005). In Spain, the potential production at national level is estimated at around 15.3 Mg DM ha À1 year À1 , for standard-management plantations covering a wide range of scenarios (Pérez-Cruzado et al, 2013). Willow is another species of the Salicaceae family which is widely used in SRC, especially in Northern Europe (Kuzovkina et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A pesar de sus requerimientos de agua, la producción industrial del chopo está particularmente bien establecida en el sur y norte de España, principalmente para la producción de madera (Tolosana et al 2011). Las plantaciones de chopo convencionales se administran en períodos de rotación que abarcan generalmente los 10-15 años, con densidades de árboles típicamente entre 350 y 700 árboles por hectárea, y el retiro del tocón al final de cada rotación (Cañellas et al 2012, Pérez-Cruzado et al 2014. Se han planteado densidades más altas (> 15.000 árboles/ha) y ciclos de rotación más rápidos para aumentar el rendimiento de biomasa a valores superiores a 35 tMS/ha·yr (Testa et al 2014).…”
Section: Escenario Híbrido Con Biomasa Sólidaunclassified
“…Se han planteado densidades más altas (> 15.000 árboles/ha) y ciclos de rotación más rápidos para aumentar el rendimiento de biomasa a valores superiores a 35 tMS/ha·yr (Testa et al 2014). Publicaciones recientes indican que el cultivo de chopo tendría el potencial para suministrar hasta un 1,0 % de la demanda de energía de España en el año 2020 (Pérez-Cruzado et al 2014).…”
Section: Escenario Híbrido Con Biomasa Sólidaunclassified